STUDI PENGEMBANGAN SISTEM PENYELARAS MANUFAKTUR UNTUK MENGONTROL KESALAHAN ANALISIS EFEK DAN MODA KEGAGALAN SUATU KEMAMPUAN MUTU PROSES MANUFAKTUR INDUSTRI KOMPONEN DENGAN KOMPUTASI CERDAS - Josowidagdo, Landjono (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
This article elaborate on such as, the prototype inspection, and further steps to introduce the idea of neural network systemâs implementation. The desain improvement that were assigned by the Manufacturing Review Board (MRB) will be proposed to aspire the computing systems that facilitates the whole decision systems on improving the production systems in the manufacturing plant. The MRB-Computing Intelligence program and application presented in this article have been included in the assessment model of the neural network system.